2017
DOI: 10.15562/phpma.v5i1.33
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated to first line antiretroviral therapy (ART) failure among HIV/AIDS patients at Sanglah Hospital, Bali

Abstract: Background and purpose: The incidence of first line ART failure is increasing in the South East Asia region. The main referral hospital in Bali has recorded an increased use of second line ART due to the first line ART failure. This study aims to explore risk factors associated to first line ART failure.Methods: A case control study was conducted among people living with HIV and AIDS at Sanglah Hospital Denpasar who started first line ART between 2004 and 2013. Cases were those who diagnosed as having clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(44 reference statements)
1
1
1
Order By: Relevance
“…Contrary to findings from several studies [15][16][17]19,39], some important socio demographic variables like age, sex and educational status were not found to be significant determinants of first line ART failure in the current study. This may be due to difference in socio demographic characteristics of study participants and socio economic differences between the study settings.…”
Section: Plos Onecontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to findings from several studies [15][16][17]19,39], some important socio demographic variables like age, sex and educational status were not found to be significant determinants of first line ART failure in the current study. This may be due to difference in socio demographic characteristics of study participants and socio economic differences between the study settings.…”
Section: Plos Onecontrasting
confidence: 99%
“…The current study has identified that patients with advanced WHO clinical stage III and IV at the time of initiation of ART were almost two times more likely to fail first-line antiretroviral treatment when compared with stage I and II baseline WHO clinical stage. This finding has similarity with the studies conducted in Sanglah Hospital, Bali Indonesia [15], Senegal [28], and in Harar public hospitals, Eastern Ethiopia [24]. This might be due the fact that advanced WHO clinical stage of HIV disease is associated with high viral load and low CD4 cell count that compromise immunity and may negatively affect response to first-line antiretroviral treatment [29].…”
Section: Plos Onesupporting
confidence: 84%
See 1 more Smart Citation